Peran Apip Dalam Penegakan Tindak Pidana Korupsi Terhadap Hasil Audit Penyalahgunaan Wewenang - Dudy, Aryadi Almau; Ashady, Suheflihusnaini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Acts of corruption are rife in government agencies both at the central and regional levels, one of the efforts to prevent corruption within the internal bodies of the government is the establishment of the APIP institution as a supervisor of policies carried out by government officials, especially in terms of abuse of office authority which results in state losses. There are two rules related to acts of abuse of office authority, namely the preventive realm in government administration which is regulated in the Act. No. 30 of 2004 and the realm of criminalization of corruption as regulated in the Act. 31 of 1999. This research departs from the point of intersection of the two laws which view the relationship between the two regulations and mutual support between one law and another. with abuse of power.The purpose of this research is to find out the role of the APIP audit in acts of abuse of authority that cause losses to the state in the perspective of corruption and how the role of the results of the APIP audit in supporting the enforcement of criminal acts of corruption and as legal evidence in the abuse of authority.